Evil perceptions but not entertainment value appraisals relate to conspiracy beliefs - Harmon-Jones, Eddie; Szymaniak, Kinga; Edgeworth, Dominic; Sebban, Gabriel; Harmon-Jones, Cindy (Frontiers in Social Psychology, 2024)
The current research examined whether the perception of evil intentions by the conspirators influences conspiracy beliefs about particular narratives. Study 1 manipulated texts describing the death of convicted sex offender Jeffrey Epstein to be either low or high in conspiratorial information. Studies 2 and 3 manipulated texts describing a fictional country's election to be either low or high in conflict. The studies revealed that the conspiratorial/antagonistic texts increased evil perceptions and conspiracy beliefs. Moreover, they revealed that perceptions of evil mediated the effect of the text condition on conspiracy beliefs. Although the studies found that the conspiratorial/antagonistic texts increased entertainment value appraisals, they did not find evidence of entertainment value mediating the effect of text condition on conspiracy beliefs. These latter results do not replicate those of van Prooijen et al. (2022). The novel results with evil perceptions suggest that perceiving that the conspirators acted with evil intentions may increase conspiracy beliefs.